PERLUKAH MANAJEMEN PERUBAHAN BAGI PEMERINTAH KABUPATEN SUMEDANG - Meltarini, Meltarini (Jurnal Politik Pemerintahan Dharma Praja, 2018)
Does Sumedang Regency need the Management of Change? This challenge question needs accurate data argumentations. Sumedang Regency is one of old regencies in West Java Province that was established under the Law Number 14 Year 1950 on the Establishment of District Areas within the Environment of West Java Province (State Gazette of the Republic of Indonesia 1950). It has a large area and a lot of potential areas. This study is conducted by using qualitative method. Cresswell (2013: 40) argued that qualitative method is an investigation process to comprehend social and human issues holistically arranged by very detail explanation toward the observed objects. The objective of this study is to know and to analyze does Sumedang Regency needs the management of change in the administration. Data is obtained through interviews and secondary data collection. The study using “if you learn you will change, but if you don’t change you will die” theory (C. K. Prahalad, 1990).